Application of drone brood in rational nutrition and apitherapy - D. V. Mitrofanov; N. V. Budnikova; A. Z. Brandorf (Аграрная наука Евро-Северо-Востока)
Drone brood is a collection of developing individuals (larvae, prepupae and pupae) of drones - males of a bee colony. Drone brood is used to produce a homogenate, which is stabilized in one way or another to achieve optimal preservation of biologically active substances. Interest in drone brood as a rich source of macro- and micronutrients is steadily increasing. The purpose of this review is to summarize the collected data on the use of drone brood in rational nutrition and apitherapy. The indicators of the quality and safety of drone brood are reviewed, the requirements of regulatory documents for products based on it are given. The necessity of strict adherence to the storage conditions of the drone brood homogenate is shown, in case of violation of which there is a rapid deterioration of the homogenate. This necessitates stabilization of the drone brood, which makes it possible to preserve its properties with lower requirements for storage conditions. The groups of nutrients that make up the drone brood and determine its biological activity and directions of application are given. Among them are lipids, including phospholipids and unique decenoic acids, proteins, peptides and amino acids, substances containing sulfhydryl groups, flavonoid and other phenolic compounds, carbohydrates, steroid substances, including hormones and hormone-like compounds, mineral elements. Products based on drone brood and biological effects of their use are described: actoprotective, anabolic, immunomodulatory, endocrinotropic, neurotropic, nutritional and cosmetic. The analyzed data indicate the high relevance of the further introduction of drone brood preparations into nutritional and apitherapeutic practice, which will serve as a tool for correcting the diet of a modern person suffering from a disease of civilization, largely associated with a violation of the ratio and amount of nutrients in the diet.